THE EFFECT OF PROJECT BASED LEARNING MODEL AND COOPERATION SKILLS ON RESULTS OF SOCIOLOGY LEARNING IN SMA 4 AMBON - Arnold Sahalessy; J L Kundre; Ferdinanda S Noya (EDU SCIENCES JOURNAL, 2020)
This study aims to determine (1) the application of the project based learning model in PUBLIC SENIOR HIGH SCHOOL 4 Ambon, (2) the application of cooperation skills in Public Senior High School 4 Ambon, (3) the results of sociology learning in Public Senior High School 4 Ambon, (4) the effect of the application of the learning model project based on learning in Public Senior High School 4 Ambon, (5) the effect of applying cooperative skills in Public Senior High School 4 Ambon, (6) the effect of applying the project based learning model of learning and collaborative skills together on the results of learning sociology at Public Senior High School 4 Ambon. This study used a quasi-experimental research design. The research subjects in this study were 60 students in grade XI IIS. The results of this study indicate that (1) there are significant differences in sociology learning outcomes between groups of students taught with project based learning models and think pair share learning models, (2) there are significant differences in sociology learning outcomes between students who have high and low cooperation skills (3) high and low cooperation skills show no interaction with sociology learning outcomes, (4) Learning model (Project Based Learning and Think-Pair-Share) with cooperation skills show significant interactions with sociology learning outcomes